A Fractal View on the Suicide Incidence of Countries (Recoletos Multidisciplinary Research Journal, 2013)
Various studies on suicide and the reasons why people commit it across cultures have been conducted. However, a global view of the suicide rates, has not been explored yet. This study will prove helpful in understanding further the effect of specific cultural and social factors of the phenomenon using Fractal Statistics. This statistical method describes the irregularity of the variable. Its appropriateness is anchored on the fact that Fractal Statistics as a tool can measure the non-normal behaviour of a data set such as those found in the suicide incidence report. The data associated with female suicide do not differmuch from country to country. However, differences in the male suicide rate are immensely observable. Causes such as family breakdown, overwork, and employment security are identified. Yet, questions linger regarding this psychological ?short circuit?, especially on the high incidence of suicide in the male population traceable to lack of cultural support and men?s unwillingness to talk about suicide..
Keywords: suicide; suicide rate; fractal dimension